Flap thickness and the risk of complications in mechanical microkeratome and femtosecond laser in situ keratomileusis: a literature review and statistical analysis - Kanclerz, Piotr; Khoramnia, Ramin (Diagnostics, 2021)
Introduction: A recent Cochrane review found no difference in visual acuity outcomes between femtosecond-assisted laser in situ keratomileusis (LASIK) and LASIK using mechanical microkeratomes (MMKs). This study compares the flap thickness and risk of complications related to flap creation using femtosecond lasers and MMKs. Methods: PubMed and the Web of Science are used to search the medical literature. An extensive search is performed to identify the flap thickness and complications of LASIK as reported up to 15 July 2021. The following keywords are used in various combinations: Corneal flap, femtosecond laser, laser in situ keratomileusis, laser-assisted in situ keratomileusis, LASIK, mechanical microkeratome. Results: After removing duplicates and irrelevant studies, 122 articles were included for review. Pooled differences for intended vs. postoperative flap thickness using MMKs and femtosecond laser were −4.07 μm (95% CI: −19.55, 3.24 μm) in studies on the MMK and 5.43 μm (95% CI: 2.30, 7.84 μm; p < 0.001), respectively. After removing the studies evaluating outcomes of the old generation Hansatome MMKs (which had a significantly greater variation of flap thickness), the pooled difference for newer MMKs was 4.97 μm (95% CI: 0.35, 9.58 μm; p < 0.001), but the results still favored the femtosecond laser. Uncommon and mild complications unique for the femtosecond LASIK are epithelial gas breakthrough, opaque bubble layer, transient light sensitivity syndrome, and rainbow glare. A single study reported a very low, but stastically different risk of postoperative flap slippage (0.033% for MMK LASIK, and 0.003% for femtosecond LASIK, respectively). Conclusion: In both manual microkeratome and femtosecond LASIK, intra- and postoperative complications were uncommon. The evidence of the superiority of one technique in terms of complications over another cannot be indisputably stated.
Gesehen am 10.11.2021
This article belongs to the special issue "Eye diseases: diagnosis and management"